Harnessing baicalein to mitigate antibiotic resistance: resensitizing norfloxacin against urinary multidrug-resistant Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa - K. P., Akhila; Omanakuttan, Akhil C.; C. P., Athira; K. N., Silpa; K. S., Harish Kumar (International Journal of Research in Medical Sciences, 2026)
Background: According to the World Health Organization (WHO) Priority Pathogen List — 2024, multidrug-resistant pathogens will emerge and spread rapidly in the coming years. This has to be countered by the urgent development of novel antibiotics for their effective management. Restoring and enhancing the potency of existing antibiotics by combining with bioactive compounds is a novel strategy to be further studied. The purpose of our study is to determine the synergistic effect of one of the active ingredients from Chinese skullcap, baicalein with norfloxacin on multi-drug resistant uropathogens. Methods: The present cross-sectional study was undertaken at School of Medical Education (SME), Kerala, India, during the period of November 2023 to November 2024. Based on the calculated FICI values, results were interpreted as Synergy (FICI≤0.5), Additive (0.5<FICI≤1), Indifferent (1<FICI≤4), Antagonistic (FICI>4). The data were analysed using Microsoft Excel software (Windows 2010). Chi-square test was performed using IBM statistical package for the social sciences (SPSS) Statistics 24 to evaluate significant differences (p value <0.05) among the parameters examined in this study. Results: A total of 150 drug-resistant strains of E. coli, K. pneumoniae and P. aeruginosa were isolated from urinary tract infections (UTIs). Resistance to norfloxacin was observed in 64% of E. coli, 68% of K. pneumoniae, and 74% of P. aeruginosa isolates. Notably, baicalein resensitized 56.3% of E. coli, 70.6% of K. pneumoniae, and 75.7% of P. aeruginosa strains to norfloxacin, as determined by the checkerboard assay and these findings were statistically significant. Conclusions: This study emphasizes the need for ongoing surveillance of antimicrobial resistance in common urinary pathogens and also suggests that natural compounds like baicalein may resensitize existing antibiotics like norfloxacin against resistant strains, warranting further research into the underlying mechanisms and potential clinical applications.